Effectiveness of chatbot application in supporting independent strength fitness training - Pashchenko, L.G.; Volkov, L.A.; Sokolova, V.V.; Pashchenko, E.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to assess the effectiveness of chatbot application as a form of pedagogical support for independently organised strength fitness training among young women. Methods and structure of the study. A pedagogical experiment was conducted involving young women aged 18-20 with no prior sports experience, aimed at studying the potential of a chatbot as a form of pedagogical support for strength fitness training. The methods employed included anthropometry, functional testing, a pedagogical experiment, and pedagogical observation. Results and conclusions. The experiment demonstrated that the intended result of reducing body circumference measurements in young women who trained according to a chatbot-generated programme, but without real-time specialist supervision, was achieved at the cost of deteriorated adaptive capacity of the body and loss of interest in using strength fitness for body composition correction. Interactive content enables the engagement and maintenance of an individual’s interest in physical education and health-enhancing activities only with the active involvement of a specialist possessing the relevant competencies.